All-trans retinoic acid downregulates HBx levels via E6-associated protein-mediated proteasomal degradation to suppress hepatitis B virus replication - Han, Jiwoo; Jang, Kyung Lib (PloS one, 2024)
All- trans retinoic acid (ATRA), recognized as the principal and most biologically potent metabolite of vitamin A, has been identified for its inhibitory effects on hepatitis B virus (HBV) replication. Nevertheless, the underlying mechanism remains elusive. The present study reveals that ATRA induces E6-associated protein (E6AP)-mediated proteasomal degradation of HBx to suppress HBV replication in human hepatoma cells in a p53-dependent pathway. For this effect, ATRA induced promoter hypomethylation of E6AP in the presence of HBx, which resulted in the upregulation of E6AP levels in HepG2 but not in Hep3B cells, emphasizing the p53-dependent nature of this effect. As a consequence, ATRA augmented the interaction between E6AP and HBx, resulting in substantial ubiquitination of HBx and consequent reduction in HBx protein levels in both the HBx overexpression system and the in vitro HBV replication model. Additionally, the knockdown of E6AP under ATRA treatment reduced the interaction between HBx and E6AP and decreased the ubiquitin-dependent proteasomal degradation of HBx, which prompted a recovery of HBV replication in the presence of ATRA, as confirmed by increased levels of intracellular HBV proteins and secreted HBV levels. This study not only contributes to the understanding of the complex interactions between ATRA, p53, E6AP, and HBx but also provides an academic basis for the clinical employment of ATRA in the treatment of HBV infection.